Effect of target sound made by one swimmer`s dolphin kick movement on another swimmer`s dolphin kick performance - Shimojo, H.; Ichikawa, H.; Tsubakimoto, S.; Takagi, H. (Biomechanics and Medicine in Swimming XI, 2010)
The aim of this study was to determine the effect of a target sound made by a model swimmer`s dolphin kick movement on another swimmer`s dolphin kick performance. Fifteen competitive swimmers participated in this study. Subjects were required to swim using a dolphin kick while listening to the target sound as closely as possible. The aim of the task was to determine whether the timing and displacement of their dolphin kick would change, and the degree to which the change would be retained without the sound. After swimming with sound, subjects experienced a decrease in timing error relative to their performance without sound for up to 300 s, but displacement error did not decrease significantly. The results also suggested that with auditory models, which have been particularly effective for timing patterns, it would be hard to recognize displacement differences.